Model Perencanaan Kehumasan Pemerintah: Pendekatan Analytical Hierarchy Process (AHP) pada BPK Perwakilan Provinsi Maluku Utara - Roni Wijaya; Hifni Alifahmi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Effective public relations planning is a critical need for government agencies in building a positive public image and reputation. This study aims to develop a public relations communication planning model using the Analytical Hierarchy Process (AHP) and Interpretive Structural Modeling (ISM) approaches for the Public Relations Division of the Audit Board of the Republic of Indonesia (BPK), North Maluku Provincial Representative Office. A qualitative approach was employed, grounded in a post-positivist paradigm. The results reveal that the key factors to consider in communication planning include the quality and relevance of news content to public interest (0.3723), coordination between internal units (0.2257), and the volume and diversity of news coverage (0.1775). Priority message themes include audit planning activities and the submission of audit reports. The most effective communication channels are the official website, followed by mass media and digital platforms such as YouTube and Facebook. Additionally, the reputation index of BPK North Maluku for the 2019–2024 period was 0.52, categorized as